Messianic Judaism : a Critical Anthology. - Cohn-Sherbok, Dan (Bloomsbury Publishing, 2000)
Who are the Messianic Jews? What do they believe and practice? What is the Jewish community''s reaction to the development of Messianic Judaism? In this pioneering study, Dan Cohn-Sherbok traces the development of the Messianic movement from ancient times to its transformation after World War II. Focusing on the nature of the movement today, the volume continues with a detailed examination of Messianic practices, and the place of Messianic Judaism within the contemporary Jewish community.